2008
DOI: 10.1089/aid.2007.0290
|View full text |Cite
|
Sign up to set email alerts
|

HTLV Type 1 Molecular Study in Brazilian Villages with African Characteristics Giving Support to the Post-Columbian Introduction Hypothesis

Abstract: We performed an HTLV epidemiological study of 986 individuals from 17 villages from the same state of Salvador, the city with the highest HTLV-1 prevalence in Brazil. The HTLV-1 prevalence was 3.85%, 1.56%, and 1.23% in three villages. Phylogenetic analysis of the LTR region demonstrated that all positive samples analyzed belonged to the Transcontinental subgroup of the HTLV-1 Cosmopolitan subtype. Three of the new HTLV-1 sequences formed a well-supported clade within one of the Latin American clusters that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
15
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
4
15
0
2
Order By: Relevance
“…This study is in agreement with findings from previous studies, 21,22,25,26,38 reaching the conclusion that the HTLV-1a Transcontinental subgroup is the most prevalent strain found in Brazil. The presence of HTLV-1 LTR sequences from Bahia in several clusters along the phylogenetic tree suggests multiple post-Columbian introductions of HTLV-1 into the Brazilian population.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…This study is in agreement with findings from previous studies, 21,22,25,26,38 reaching the conclusion that the HTLV-1a Transcontinental subgroup is the most prevalent strain found in Brazil. The presence of HTLV-1 LTR sequences from Bahia in several clusters along the phylogenetic tree suggests multiple post-Columbian introductions of HTLV-1 into the Brazilian population.…”
supporting
confidence: 93%
“…The presence of HTLV-1 LTR sequences from Bahia in several clusters along the phylogenetic tree suggests multiple post-Columbian introductions of HTLV-1 into the Brazilian population. These data, in addition to other studies from regions throughout Bahia, 25,26 serve to confirm the postColumbian introduction hypothesis of HTLV-1 into Bahia.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…A recent phylogenetic study suggests that West African hepatitis B virus (HBV) lineages were introduced to Haiti during the peak years of slave movement (1). Similarly, recent studies of human T-cell leukemia virus type 1 (HTLV-1), which sometimes combine human and viral evidence, have indicated that Surinamese, Guyanan, Brazilian, Argentinian, and Peruvian HTLV-1 lineages grouped among West African lineages (3,12,32).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 HTLV-1 is widespread in the northeast region of Brazil, 3,4 and studies on its origin and dissemination showed that HTLV-1 was recently introduced in this region, most likely through the post-Columbian migrations of the African slave trade between the sixteenth and nineteenth centuries. 5,6 HTLV-1 has also been detected in other regions of the country, but with a smaller percentage of cases than in the northeast. 4 The molecular characterization of HTLV-1 in Brazil showed that the Cosmopolitan subtype (a) of transcontinental subgroup A was prevalent, although historical data indicated that the slave trade movement originated from west Africa, where only the western African subgroup (C) circulates.…”
mentioning
confidence: 99%